Improvements to emergency department length of stay and user satisfaction after implementation of an integrated consult order - Akshay Ravi; Guy Shochat; Ralph C. Wang; Raman Khanna (Journal of the American College of Emergency Physicians Open)
Abstract Objective Subspecialty consultation in the emergency department (ED) is a vital, albeit time consuming, part of modern medicine. Traditional consultation requires manual paging to initiate communication. Although consult orders through the electronic health record (EHR) may help, they do not facilitate 2‐way communication. However, the impact of combining these systems within the EHR is unknown. We estimated the effect of implementing an integrated paging system on ED workflow efficiency and user attitudes. Methods We integrated a messaging system into order entry at our tertiary care academic ED, such that placing a consult order simultaneously paged the consultant. We measured ED workflow efficiency metrics (length of stay [LOS], consult initiation time) and MD/nurse practitioner (NP)/physician assistant (PA) attitudes (perceived mis‐pages, efficiency, and workflow preference) 3 months before and 6 months after the implementation. Results Six months after implementation, there was 25% use of the new workflow. During the pre‐implementation phase, the median time to consult initiation and ED LOS were 150 and 621 minutes, respectively. Implementation of the order was associated with a 15‐minute reduction in median time to consult initiation (P < 0.001), and a 52‐minute reduction in median ED LOS (P < 0.001). ED MDs/NPs/PAs perceived a reduction in the rate of mis‐pages, improved efficiency, and overall preferred the new workflow. Conclusions We consolidated steps in the ED consult workflow using an integrated consult order, which improved user satisfaction, and reduced consult initiation time and ED LOS for patients requiring a consult at an urban tertiary care ED.